Electroencephalography and Eye Gaze Movement Signals’ Usage for Estimation of User Interface Usability - Radvile, Egle; Cenys, Antanas; Ramanauskaite, Simona (Elektronika ir Elektrotechnika, 2015)
Task execution time is one of components used to estimate system’s usability. Since information search is one of the most important tasks in any computer system, the eye movement should be taken into account while designing system’s interface. Fitts’ law allows to estimate probable eye movement time based on the distance between objects and their size. User’s motivation can significantly influence the eye movement speed. In this paper we analyze experimentally how Fitts’ law parameter (slope) changes when user is motivated and when there is less motivation to execute the task. Our experiments confirm that gamma brainwave activity can be used as a metric to estimate the motivation level. This allows a more objective estimation of the motivation level as compared to situation when motivation level is estimated by an expert’s observation. It is also demonstrated that the slope in Fitts’ law is up to five times smaller when children of age two to four years are motivated to reach the object and the motivation can be raised by presenting new, unseen objects. Obtained results allow a more precise estimation of the eye movement task execution time as well as provide additional insights for system interface designers aiming to attract small children.DOI: http://dx.doi.org/10.5755/j01.eee.21.5.12511